Value of implanting and reimplanting feedlot heifers - S. Laudert; Gerry L. Kuhl; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1983)
Implanting incoming feedlot heifers with Ralgro® or Synovex-H® increased weight gain an average of 9.4%. Reimplanting half way through the 119 day feeding period did not improve gain significantly. There were no differences between Ralgro and Synovex-H when used as the initial or second implant.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Implants; Reimplanting; Feedlot heifers